Silage making of maize stover and banana pseudostem under South Ethiopian conditions: evolution of pH, dry matter and microbiological profile. Issue 5 (24th July 2020) - Mitiku, Ashenafi Azage; Andeta, Addisu Fekadu; Borremans, An; Lievens, Bart; Bossaert, Sofie; Crauwels, Sam; Aernouts, Ben; Kechero, Yisehak; Van Campenhout, Leen
Summary: The study was conducted to evaluate the microbial dynamics during silage of maize stover and banana pseudostem in the environmental conditions of southern Ethiopia. To meet this objective, microsilos containing either maize stover or banana pseudostem, both with and without molasses, were prepared. Subsequently, samples were analysed on day 0, 7, 14, 30, 60 and 90 of the fermentation process. As a result, on day 7, all treatments except banana pseudostem without molasses showed a significant reduction in pH. It was also this silage type that supported the growth of Enterobacteriaceae longer than three other silage types, i.e. until 30 days. The yeasts and moulds and the Clostridum endospore counts also showed a reducing trend in early fermentation and afterwards remained constant until day 90. Illumina MiSeq sequencing revealed that Leuconostoc, Buttiauxella species and Enterobacteriaceae were the most abundant bacteria in the initial phases of the fermentation. Later on, Buttiauxella, Lactobacillus, Weissella and Bifidobacterium species were found to be dominant. In conclusion, silage of the two crop by‐products is possible under South Ethiopian conditions. For banana pseudostem, the addition of molasses is crucial for a fast fermentation, in contrast to maize. Upscaling needs to be investigated for the two by‐products. Abstract : Maize and Banana pseudostem by‐products can be considered as potential options in silage making under the environmental conditions of Ethiopia. Fermentation of banana pseudostem requires molasses to obtain a fast pH reduction.